Dr. Miguel Martínez Miguelez interview (Publicaciones en Ciencias y Tecnología, 2013)
Interview to Dr. Miguel Martínez Miguélez, Doctor in Pedagogy from the Salesian Pontifical University of Rome with a Specialization in Educational Psychology. He is Professor-Researcher (Retired) at the Simón Bolívar University of Caracas and responsible for the research line "Philosophy of Science and Qualitative Methodology".
Keywords: interview; Martínez-Miguelez